Evaluating the Green Campus Program at Universitas Padjadjaran Using the UI GreenMetric Framework - Eva Lesty Lina Lewi; Arie Pratama; Annisa Nabila Hasan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study evaluates the implementation of the Green Campus program at Universitas Padjadjaran (Unpad) and its contribution to sustainability performance based on the UI GreenMetric framework. Despite the growing adoption of sustainability initiatives among Indonesian universities, challenges remain in translating policies into effective implementation. Using a descriptive qualitative approach with an evaluative method, this research applies six UI GreenMetric indicators such as: Setting and Infrastructure, Energy and Climate Change, Waste, Water, Transportation, and Education and Research as the analytical framework. Data were collected through document analysis and institutional reports. The results indicate that Unpad demonstrates strong performance in the Energy and Climate Change as well as Education and Research indicators, reflecting significant progress in energy efficiency policies and the integration of sustainability into academic activities. However, relatively lower scores in Water and Setting and Infrastructure highlight challenges related to water management systems and the equitable distribution of green infrastructure across campuses. Supporting factors include institutional commitment, policy integration, and participation in sustainability rankings, while constraints involve unequal distribution of program across campuses, financial capacity and budget allocation, as well as infrastructure limitations. Overall, the findings indicate that the Green Campus program has shown a meaningful contribution to strengthening Unpad’s sustainability performance, although further optimization is required to ensure more comprehensive and balanced implementation across all indicators.